Biotechnology: a powerful tool for the removal of cadmium from aquatic systems - Munawar, Rabeea; Mughal, Ehsan Ullah; Sadiq, Amina; Mukhtar, Hamid; Zafar, Muhammad Naveed; Mumtaz, Muhammad Waseem; Ahmed, Ishtiaq; Muhammad Zubair,; Ahmad Khan, Bilal; Ashraf, Jamshaid; Yousaf, Zofishan; Akbar, Noreed (Penerbit Universiti Kebangsaan Malaysia, 2018)
The prime objective of the present research work was to evaluate the efficiency of bio-machine for the removal of Cadmium (Cd) from aquatic systems. Aspergillus niger fungus was used as bio-machine to remove Cd from aquatic systems. Twenty three different strains (IIB-1 to IIB-23) were isolated from industrial effluents and the Langmuir and Freundlich models were applied to the best Cadmium removal strain IIB-23 in order to obtain the adsorption parameters. Different parameters such as pH, temperatur e, contact time, initial metal concentratio, and biomass dosage on the biosorption of Cd were studied. The percent removal of Cd initially increased with an increase in pH ranging from 5.5-6.5 and then decreased by increasing pH from 7.0-7.5. An optimized pH used for Cd removal from aquatic systems was found to be 6.5. Additionally, an optimum amount of biomass was 1.33 g for the maximum removal of Cd from the aqueous solutions with initial metal concentration of 75 mg/L. The results obtained thus indicated that Langmuir model is the best suited for the removal of Cd from aquatic systems.